Contemporary Pastoral Praxis: Addressing Structural Injustice in Nomzamo Park Informal Settlement, Soweto - Solomon Sipho Mahlangu, PhD (Pharos Journal of Theology)
This article examines contemporary pastoral praxis in addressing structural injustice within the Nomzamo Park informal settlement in Soweto, South Africa, contributing to the contextualization of practical theology and pastoral care in the African context. Nomzamo Park, which is characterized by its socio-economic challenges and systemic inequalities, serves as a focal point for exploring how pastoral care can effectively respond to the needs of marginalized communities. The study highlights the intersection of faith and social justice, emphasizing the role of the church in advocating for structural change and providing holistic support to residents. Utilizing a practical theological framework, the research draws on qualitative data from interviews and participant observations, revealing the lived experiences of community members and their interactions with pastoral initiatives. The findings suggest that effective pastoral praxis in Nomzamo Park involves a critical engagement with social issues, fostering community resilience, and promoting advocacy for justice. Pastoral care is re-envisioned not merely as spiritual support but as an active, transformative presence addressing poverty, housing insecurity, and other systemic injustices. This approach aligns with the broader objectives of Practical Theology, which seeks to integrate theological reflection with practical action in real-world contexts. Moreover, this article underscores the importance of culturally sensitive pastoral strategies that resonate with the unique experiences and needs of African communities. It argues for a praxis that is both contextually relevant and theologically sound, advocating for the church's role in spearheading initiatives that challenge oppressive structures while nurturing the spiritual and material well-being of individuals. In conclusion, this article calls for an expanded understanding of pastoral care that embraces social justice as a core component, thereby enriching the discourse on Practical Theology in the African context and offering insights for similar settings globally.